Tata Kelola Perusahaan Yang Baik: Sebagai Upaya Penguatan BUMN - Vidya Kartika Ayuningtias; Elisatris Gultom (Hakim, 2024)
This paper aims to see the application of Good Corporate Governance principles as an effort to strengthen SOEs. The Principles of Good Corporate Governance are the principles that underline a company's management processes and mechanisms based on laws and regulations and business ethics. SOEs as a business entity have so far only played a development role in their journey so that they often ignore the role of SOEs as a business entity or business operator, which causes the management of SOEs to be considered less successful. Therefore, the implementation of Good Corporate Governance principles is expected to strengthen SOEs as a Business Entity. This research uses normative juridical approach method of analytical descriptive research specification. The data is collected through literature and refers to the provisions of laws and regulations. This study concludes that the Principles of Good Corporate Governance are needed to be applied as an effort to link SOEs as Business Entities which includes application in several aspects, namely especially shareholder rights, equal treatment of shareholders, the role of shareholders that must be recognized, accurate and timely disclosure, and board responsibility.